Strategic marketing management : text and cases - Ferrell, O. C. (College Division, 1994)
This book is about: An overview of strategic marketing management; The role of information analysis in marketing strategy; Utilizing SWOT as a foundation for planning; Marketing ethics and social responsibility in strategic market planning; ...